Oral and Poster Abstract Sessions 2018
DOI: 10.1136/oemed-2018-icohabstracts.887
|View full text |Cite
|
Sign up to set email alerts
|

72 Assessment of child labour in agriculture among syrian refugees in lebanon

Abstract: diseases (n=538). Considering just the diabetes ICDs, Insulindependent diabetes mellitus (E10) represented 63.6%, followed by non-insulin-dependent Diabetes (E11) with 24.4% and unspecified diabetes mellitus (E14) with 12%. The majority of beneficiaries were male (71.7%), associated with urban jobs (46.7%) especially administrative posts, ranging from 50 to 64 years old (63%). Discussion The profile of workers who have requested benefits due to diabetes mellitus showed that the majority of beneficiaries were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It follows the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines (See S1 STROBE checklist ). The study methodology is also described in recently published articles [ 3 , 17 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines (See S1 STROBE checklist ). The study methodology is also described in recently published articles [ 3 , 17 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following the Syrian war, the cross-border labor migration ceased, and Syrians became permanent refugees in Lebanon [ 2 ]. Today, many Syrian refugee families living in the Bekaa send their children to work in agriculture as well as various other sectors [ 3 ]. Many live in extreme poverty in informal tented settlements, lacking basic needs and proper housing, rendering them one of the most vulnerable populations in the country [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the reviewed studies reported that children of migrant workers are more likely to enter into child labor or engage with household work which affects their ability to continue their education ( 29 ). According to UNICEF, 36.5 million children were displaced from their homes by the end of 2021 as a result of conflict, violence, and other crises ( 67 , 68 ). Children who migrate alone are at a high risk of falling into child labor or being trafficked for sexual exploitation ( 69 ).…”
Section: Discussionmentioning
confidence: 99%